Effectiveness of Herbal Diet Nigella sativa and Gracilaria verrucosa Against Non-specific Immunity of Tilapia (Oreochromis niloticus) - Purbomartono, Cahyono; Rofiqoh, Rofiqoh; Husin, Arief; Mulia, Dini Siswani (Sainteks, 2023)
The addition of Nigella sativa and Gracilaria verrucosa to feed is used as a supplement to increase non-specific immunity in tilapia. The addition of herbal supplements is safe for consumption, easy to decompose, has no residue on the fish's body, and does not harm the environment. This study aims to find the effectiveness of the addition of the herbs Nigella sativa and Gracilaria verrucosa to increase non-specific immunity in tilapia. The study used an experimental method with a completely randomized design, applying 4 treatments and 1 control to tilapia. The dietary doses of Nigella sativa were T0 (control, without Nigella sativa), T1 (2.5), T2 (5), T3 (7.5), and T4 (10) (g kg-1 feed). While the dietary doses of Gracilaria verrucosa were T0 (control, without G. verrucosa), T1 (0.5), T2 (1), T3 (1.5), and T4 (2) (g kg-1 feed). The results showed that the percentage of hematocrite increased significantly with the Nigella sativa diet, while on the Gracilaria verrucosa diet, the percentage of hematocrit was not significant. Further, the Nigella sativa diet and the Gracilaria verrucosa diet can significantly increase the percentage of lymphocytes, but not significantly to the percentage of monocytes. In fish farming, the Nigella sativa and Gracilaria verrucosa diets have the potential to be used to increase non-specific immunity in tilapia, but it is more effective to use the Nigella sativa diet at a dose of 5 g kg-1 feed.